Cesium-ion-doped strontium-iron-based perovskite solid oxide electrolytic cell cathode material as well as preparation method and application of cesium-ion-doped strontium-iron-based perovskite solid oxide electrolytic cell cathode material

By introducing cesium ion doping into the SOEC cathode material, Cs0.1Sr0.9Fe0.9Nb0.1O3-δ material was prepared, which solved the problem of insufficient CO2 adsorption and dissociation activity of the existing SOEC cathode material, significantly improved the oxygen ion mobility and electrolytic activity, and achieved excellent SOEC performance.

CN119612596APending Publication Date: 2025-03-14NANJING TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411488305.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing solid oxide electrolytic cell (SOEC) cathode materials have problems such as insufficient CO2 adsorption and dissociation activity and low oxygen ion phase migration ability during CO2 electrolysis, which affects the electrolytic activity.

Method used

The cathode material of strontium iron-based perovskite solid oxide electrolytic cell doped with cesium ion was prepared by the sol-gel method to improve its CO2 adsorption and dissociation activity and oxygen ion phase migration ability.

Benefits of technology

It significantly improves the CO2 adsorption and dissociation capabilities of the material, enhances the migration ability of oxygen ions in the material body phase, improves the electrolytic activity of the SOEC cathode, and shows excellent performance under different temperature and voltage conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612596A_ABST
    Figure CN119612596A_ABST
Patent Text Reader

Abstract

The invention relates to a novel Cs1 < + >-doped strontium-iron-based perovskite solid oxide electrolytic cell cathode material, and belongs to the field of solid oxide electrolytic cell cathode materials. Adsorption and dissociation of CO2 molecules on the surface of the cathode material during operation of the electrolytic tank are promoted through doping of Cs1 +. The doping of Cs1 < + > is also beneficial to the generation of oxygen vacancies in the strontium-iron-based perovskite and promotes the transmission rate of oxygen ions in a cathode bulk phase. And the electrolytic performance of the electrolytic tank is 2205 mA cm <-2 > and the electrode impedance is 0.18 ohm cm < 2 > at 850 DEG C and 1.6 V external voltage. The battery can stably operate for 100 hours at the temperature of 800 DEG C and under the impressed current of 600mA cm <-2 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a solid oxide electrolytic cell cathode material and a preparation method and application thereof, and in particular to a cesium ion-doped strontium iron-based perovskite solid oxide electrolytic cell cathode material and a preparation method and application thereof. Background Art

[0002] The greenhouse effect caused by excessive CO2 emissions has caused climate problems. Therefore, it is important to reduce the CO2 content in the atmosphere. Solid oxide electrolysis cell (SOEC) is a technical means to effectively convert CO2. It can use electricity obtained from renewable energy to convert CO2 into value-added CO at high temperature for use as a raw material in the chemical industry. SOEC has the advantages of high Faraday efficiency and fast thermodynamic and kinetic rates, so it has been widely studied. In the process of using SOEC to electrolyze CO2, CO2 will first be adsorbed on the surface of the cathode material to form a carbonate intermediate species, which will then gain electrons, and CO2 will dissociate into CO and O at the same time. 2- Subsequently, CO dissociates from the electrode surface and O 2- It will be transferred to the anode side through the electrode bulk phase and the electrode / electrolyte interface and precipitated in the form of oxygen. The adsorption and dissociation of CO2 are crucial for the reaction on the cathode side of SOEC. In addition, since the cathode thickness is generally around ten microns, the migration path of oxygen ions in the electrode bulk is relatively long, which will also affect the electrolytic activity of SOEC. The reaction on the cathode side has an important influence on the reaction activity of SOEC. Therefore, the development of electrode materials with high electrode reaction process rates and ion bulk migration rates is crucial for the further development of SOEC. Summary of the invention

[0003] The purpose of the present invention is to provide a solid oxide electrolytic cell perovskite cathode material Cs 0.1 Sr 0.9 Fe 0.9 Nb 0.1 O 3-δ The invention relates to a preparation method and application thereof to improve the problem of insufficient performance of existing cathode materials. The material has excellent CO2 adsorption and dissociation activity and improved oxygen ion phase migration ability.

[0004] The technical solution is:

[0005] A cesium ion-doped strontium iron-based perovskite solid oxide electrolytic cell cathode material having the following chemical formula: Cs x Sr y Fe z Nb m O 3-δ, δ is the oxygen vacancy; 0.05≤x≤0.15, 0.85≤y≤0.95, 0.85≤z≤0.95, 0.05≤m≤0.15.

[0006] The chemical formula is Cs 0.1 Sr 0.9 Fe 0.9 Nb 0.1 O 3-δ .

[0007] The cathode material is prepared by a sol-gel method.

[0008] In the sol-gel method, citric acid is first dissolved in deionized water, and then niobium oxalate is added. After the dissolution, strontium nitrate, cesium nitrate and ferric nitrate are dissolved, and then a solution of ethylenediaminetetraacetic acid dissolved in ammonia water is added to the above metal ion solution. The water is evaporated under heating and stirring conditions to obtain a gel-like substance. The gel-like substance is placed in an oven for drying to obtain a material precursor, and then the precursor is placed in a muffle furnace for calcination to obtain a phased powder.

[0009] The conditions of the calcination process are: calcination temperature is 950-1050°C, and calcination time is 3-8 hours.

[0010] The total molar ratio of ethylenediaminetetraacetic acid, citric acid and metal ions is 2:0.8-1.2:0.8-1.2.

[0011] The drying temperature of the precursor is 150-200°C and the drying time is 3-8 hours.

[0012] Application of the above solid oxide electrolytic cell cathode material in CO2 electrolysis.

[0013] A method to increase SrFe 0.9 Nb 0.1 O 3-δ The method to improve the surface oxygen vacancies of (SFN) materials or the adsorption and dissociation properties of CO2 is through doping the oxide with cesium ions.

[0014] Beneficial Effects

[0015] A new solid oxide electrolytic cell cathode material Cs was obtained by sol-gel method. x Sr y Fe z Nb m O 3-δ , it can be found through CO2 programmed temperature desorption that Cs 1+ The introduction of ions significantly improves the CO2 adsorption and dissociation capabilities of the material. Synchrotron radiation X-ray absorption spectroscopy proves that Cs 1+Ion doping can increase the oxygen vacancy concentration of the material, thereby promoting the migration of oxygen ions in the bulk phase of the material. When used in an electrolytic cell supported by LSGM electrolyte, it showed excellent performance, with current densities of 2200, 1330, 818, and 530 mA cm at 850°C, 800°C, 750°C, 700°C, and 1.6 V applied voltage, respectively. -2 . BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 SrFe with different Cs doping ratios 0.9 Nb 0.1 O 3-δ (SFN),Cs 0.05 Sr 0.95 Fe 0.9 Nb 0.1 O 3-δ (CSFN0.05),Cs 0.1 Sr 0.9 Fe 0.9 Nb 0.1 O 3-δ (CSFN0.1),Cs 0.15 Sr 0.85 Fe 0.9 Nb 0.1 O 3-δ (CSFN0.15) X-ray diffraction (XRD) refinement pattern.

[0017] Figure 2 It is a bar graph showing the change in the unit cell volume of the material as the amount of Cs ion doping increases.

[0018] Figure 3 These are scanning electron microscope (SEM) images of SFN, CSFN0.05, CSFN0.1, and CSFN0.15.

[0019] Figure 4 This is a high-magnification transmission electron microscopy (TME) image of CSFN0.1.

[0020] Figure 5 This is the TEM energy spectrum of CSFN0.1.

[0021] Figure 6 This is the high temperature XRD pattern of CSFN0.1.

[0022] Figure 7 It is the synchrotron radiation X-ray absorption structure spectrum (XAS) of SFN and CSFN0.1.

[0023] Figure 8It is the X-ray photoelectron spectrum (XPS) of SFN, CSFN0.05, CSFN0.1 and CSFN0.15.

[0024] Fig. 9 These are the in situ infrared spectra of SFN, CSFN0.05, CSFN0.1, and CSFN0.15.

[0025] Fig.10 These are the CO2 temperature-programmed desorption (CO2-TPD) and CO temperature-programmed desorption (CO-TPD) diagrams of SFN, CSFN0.05, CSFN0.1, and CSFN0.15.

[0026] Fig.11 It is the electrochemical impedance spectrum (EIS) of symmetric cells of SFN, CSFN0.05, CSFN0.1 and CSFN0.15.

[0027] Fig.12 It is the single electrolytic cell current density diagram, current-voltage (IV) curve diagram and single electrolytic cell EIS of SFN, CSFN0.05, CSFN0.1 and CSFN0.15.

[0028] Fig.13 These are the stability test, CO yield test and Faraday efficiency test charts of SFN and CSFN0.1.

[0029] Fig.14 This is a schematic diagram of the technical principle of the oxide material in the patent. DETAILED DESCRIPTION

[0030] Example 1 Preparation of cathode materials SFN, CSFN0.05, CSFN0.1, CSFN0.15

[0031] (1) Weigh 43 g of citric acid and 0.05 mol of niobium oxalate according to the stoichiometric ratio in the molecular formula, add them into a beaker, and add water to dissolve them.

[0032] (2) Weigh 0.05 mol of strontium nitrate, cesium nitrate, and iron nitrate and add them to the above solution to dissolve.

[0033] (3) Dissolve 30 g of EDTA in 100 ml of aqueous ammonia.

[0034] (4) After the above metal ions are completely dissolved, an aqueous ammonia solution containing ethylenediaminetetraacetic acid is added to the metal ion solution for complexation, and an appropriate amount of aqueous ammonia is added dropwise to make the solution pH reach between 7 and 8. Subsequently, the water is completely evaporated under magnetic stirring to obtain a gel-like substance.

[0035] (5) The gel-like substance is placed in an oven and calcined at 180°C for 5 h to obtain the desired foam precursor.

[0036] (6) The precursor is placed in a high-temperature muffle furnace and calcined at 1000°C for 5 hours to obtain the desired powder.

[0037] Example 2 Preparation of symmetrical battery

[0038] (1) Weigh 1 g of the powder prepared in Example 1, 10 ml of isopropanol, 2 ml of ethylene glycol, and 0.8 ml of propylene glycol, pour them into a high-energy ball mill, and ball mill them at 400 r / min for 30 min. Transfer them to the culture bottle with a dropper to obtain the desired cathode slurry.

[0039] (2) The prepared LSGM electrolyte was placed on a heating table and preheated at 150°C. The prepared cathode slurry was evenly sprayed on both sides of the electrolyte using a spray gun under the push of inert gas. After the liquid evaporated completely, the sprayed electrolyte was placed in a high-temperature muffle furnace and calcined at 1000°C for 2 hours to obtain the required symmetrical battery, which was used for impedance testing of cathode materials in the temperature range of 700-850°C.

[0040] Example 3 Preparation of single cell

[0041] (1) Weigh 1 g of the cathode powder prepared in Example 1, 10 ml of isopropanol, 2 ml of ethylene glycol, and 0.8 ml of propylene glycol, pour them into a high-energy ball mill, and ball mill them at 400 r / min for 30 min. Transfer them to the culture bottle with a dropper to obtain the desired cathode slurry.

[0042] (2) Ba prepared by the sol-gel method 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ Pour the powder, 10 ml of isopropanol, 2 ml of ethylene glycol and 0.8 ml of propylene glycol into a high-energy ball mill, mill at 400 r / min for 30 min, and transfer to the culture bottle with a dropper to obtain the required anode slurry.

[0043] (3) The prepared LSGM electrolyte sheet is placed on a heating table, and the prepared cathode slurry is evenly sprayed on the electrolyte surface of the dry pressed sheet using a spray gun under the push of inert gas. After the liquid evaporates completely, the prepared anode slurry is evenly sprayed on the other side of the electrolyte sheet. After the anode slurry evaporates completely, the sprayed battery is placed in a high-temperature muffle furnace and calcined at 1000°C for 2 hours to obtain the desired single cell.

[0044] Characterization results:

[0045] 1. X-ray diffraction (XRD) characterization

[0046] Figure 1 The XRD refinement patterns of SFN, CSFN0.05, CSFN0.1, and CSFN0.15 are shown in the figure. As shown in the figure, these materials have a good cubic structure, the space group is Pm-3m, and there are no additional diffraction peaks in the figure.

[0047] 2. Changes in unit cell volume

[0048] Figure 2 It means Cs 1+ The effect of ion doping on the unit cell volume is shown in the figure. As Cs 1+ As the doping amount increases, the lattice volume changes from SFN Gradually increase to CSFN0.15 Indicates Cs 1+ Successful doping.

[0049] 3. Scanning Electron Microscope (SEM) Characterization

[0050] from Figure 3 It can be seen that SFN, CSFN0.05, CSFN0.1, and CSFN0.15 materials all present a porous morphology, which is a necessary condition for high electrode porosity. High electrode porosity can ensure good diffusion of gas in the electrode and ensure the mass transfer rate during the operation of the electrolytic cell.

[0051] 4. Transmission Electron Microscopy (TEM) Characterization

[0052] from Figure 4 It can be seen from the high-magnification TEM image that the CSFN0.1 crystal plane is clearly exposed, indicating that the material has a good cubic structure. The lattice spacings of 0.224, 0.274, and 0.194 nm correspond to (1 1 1), (0 1 1), and (1 1 1) of CSFN0.1, respectively.

[0053] and (0 0 2) crystal planes, which is consistent with the results of XRD refinement.

[0054] 5. TEM spectrum characterization

[0055] Figure 5 This is the TEM element distribution diagram of PSFCM0.35. From the figure, we can see that the elements Cs, Sr, Fe, and Nb are evenly distributed in the material, indicating that there is no element segregation in the material.

[0056] 6. High temperature X-ray diffraction (HT-XRD) characterization

[0057] like Figure 6As shown in the figure, no new diffraction peaks appear in the XRD spectrum of CSFN0.1 during the heating and cooling process, indicating that the crystal structure of the material is stable at high temperatures. During the heating process, the diffraction peak slightly shifts to a lower 2θ angle, and during the cooling process, it shifts to a higher 2θ angle, which is derived from the lattice expansion or contraction caused by the change in the valence and spin state of the iron ions.

[0058] 7. Synchrotron radiation X-ray absorption structure (XAS) characterization.

[0059] We investigated the electronic and coordination structures of SFN and CSFN0.1 samples by X-ray near-edge absorption spectroscopy (XANES) and extended edge absorption spectroscopy (EXAFS), which helped to determine the Cs 1+ The influence of doping. The XANES of Fe K edge is as follows Figure 7 As shown in a, compared with SFN, the absorption edge of Fe in CSFN0.1 shifts toward the low energy direction, indicating that the valence of Fe ions in CSFN0.1 is slightly lower than that in SFN. According to the principle of electrical neutrality, the reduction of Fe ion valence is accompanied by the release of perovskite lattice oxygen, that is, the generation of oxygen vacancies. In addition, from EXAFS ( Figure 7 As can be seen from Figure b), the intensity of the Fe-O coordination peak in CSFN0.1 is lower than that in SFN, which further indicates that the oxygen vacancy content in the CSFN0.1 sample increases. Therefore, we can conclude that the introduction of Cs 1+ After that, the concentration of oxygen vacancies inside the perovskite increases.

[0060] 8. X-ray Photoelectron Spectroscopy (XPS) Characterization

[0061] We used XPS to study the surface oxygen concentration in SFN, CSFN0.05, CSFN0.1, and CSFN0.15. Figure 8 As shown in Figure 2, we deconvoluted the XPS curve of the O1s orbital to determine the content of different oxygen species. The deconvoluted peaks at low, medium, and high binding energies correspond to lattice oxygen (O lat. ), adsorption of oxygen (O2 2- / O - ) and hydroxyl / carbonate (OH - / CO3 2- ).

[0062] With Cs 1+ The increase of doping amount increases the content of adsorbed oxygen and hydroxyl / carbonate, which is 54% in SFN and 59% in CSFN0.15, indicating that Cs 1+ Doping is beneficial to the formation of surface oxygen vacancies, which is consistent with the XANES and EXAFS results.1+ As the doping content increases, the binding energy of lattice oxygen decreases.

[0063] For example, the lattice oxygen binding energy of SFN is 529.14 eV, while that of CSFN0.15 is 529.01 eV. This indicates that the introduction of Cs into the lattice 1+ After that, the electron cloud density of lattice oxygen increases and the lattice oxygen basicity increases. This result can be attributed to the lower electronegativity of cesium (0.79) than that of strontium (0.95). During the CO2 electrolysis process, Lewis-acidic CO2 molecules tend to combine with oxygen vacancies and Lewis-basic lattice oxygen to form CO3 2- intermediates, which then further decompose. The increase in the basicity of lattice oxygen and the concentration of oxygen vacancies helps to accelerate the chemical adsorption and subsequent charge transfer during the CO2 reduction process. Therefore, the introduction of Cs 1+ Crucial for accelerating the surface reaction kinetics of CO2 reduction in SOEC

[0064] 9. Fourier transform infrared spectroscopy (FT-IR) characterization

[0065] We used in situ Fourier transform infrared spectroscopy to study the adsorption capacity of SFN, CSFN0.05, CSFN0.1, and CSFN0.15 for CO2. Fig. 9 As shown, after the atmosphere was switched from air to CO2 for 20 min, the absorption peak intensity representing carbonate and active carbonate intermediates increased with the increase of Cs 1+ The increase of doping amount gradually increases. 1+ The introduction of lattice helps to enhance the adsorption of CO2 by the material. This is because, compared with Sr 2+ , Cs 1+ The alkalinity of Cs is higher. In addition, the difference in the adsorption peak intensity between CSFN0.1 and CSFN0.15 is small compared with the difference in peak intensity between CSFN0.05 and CSFN0.1. This result shows that when Cs 1+ When the doping amount exceeds 0.1, the adsorption of CO2 by the material is close to saturation, which means that there may be an optimal Cs 1+ Doping amount.

[0066] 10. Mass spectrometry test

[0067] We further evaluated the CO2 adsorption activity by CO2 temperature-programmed desorption (CO2-TPD). Fig.10 As shown in a, it can be seen that the introduction of Cs into the lattice 1+ It is beneficial to increase CO2 adsorption. However, the CO2 desorption peak areas of CSFN0.1 and CSFN0.15 are very close, and the peak integrated intensity of CSFN0.1 is 5.63×10-7 The peak integrated intensity of CSFN0.15 is 5.37×10 -7 This shows that when Cs 1+ When the doping amount reaches 10 mol%, the adsorption of CO2 is basically saturated, which is consistent with the in-situ FT-IR results. In the process of CO2 electrolysis by SOEC, the desorption peak of product CO is also an important factor. Therefore, we used CO-TPD to study the adsorption of Cs 1+ Effect of doping on CO desorption. Fig.10 As shown in b, the CO adsorption amount increases with the Cs 1+ The adsorption of CO increased with the increase of doping amount, and no obvious saturation occurred. However, the adsorption of CO was lower than that of CO2. For example, the peak integral area of ​​CO2 adsorption by CSFN0.1 was 5.63×10 -7 The peak integrated area for CO adsorption is 2.57×10 -7 , indicating that Cs 1+ Based on the above results, we can draw the following conclusion: 1+ The adsorption of CO2 is more obviously promoted by doping, but the adsorption of CO2 is saturated, and the adsorption amount of CO is similar to that of Cs 1+ The doping amount is proportional to the Cs 1+ There is an optimal doping level of 0.1.

[0068] 11. Symmetrical battery test

[0069] We evaluated the catalytic activities of SFN, CSFN0.05, CSFN0.1, and CSFN0.15 electrodes in a symmetrical cell supported by LSGM electrolyte in a 50% CO–50% CO2 atmosphere. The electrochemical impedance spectroscopy (EIS) of the CSFN0.1 electrode is shown in Figure 2. Fig.11 As shown in a, the polarization resistance (Rp) at 850, 800, 750, and 700°C is 0.72, 1.79, 4.62, and 11.84 Ωcm, respectively. 2 . Fig.11 b shows the EIS graph of each electrode at 850℃. The results show that compared with SFN (1.15Ωcm 2 )、CSFN0.05(0.88Ωcm 2 ) and CSFN0.05(0.77Ωcm 2 ) electrode, CSFN0.1 (0.72Ωcm2) has the lowest polarization impedance. We use the distribution relaxation time (DRT) technique to deconvolute the EIS graph to determine the contribution of the electrode reaction process to the electrode impedance. The DRT curves of each electrode at 850℃ are shown in Figure 2. Fig.11As shown in c. It can be seen that the DRT curve is mainly composed of three peaks in different frequency ranges, which correspond to specific electrochemical processes in the CO2 reduction process. Generally, the low-frequency (LF) peak corresponds to the CO2 adsorption and dissociation process on the electrode surface, while the O 2- Migration processes inside the electrode and at the electrode / electrolyte interface are usually associated with intermediate frequency (IF) and low frequency (LF) peaks. Compared with SFN, the LF and IF peak areas of CSFN0.05, CSFN0.1, and CSFN0.15 are reduced. This indicates that Cs 1+

[0070] The increase in basicity, oxygen vacancy concentration, and metal-oxygen bond energy caused by doping effectively accelerated the reduction of CO2 and O 2- Bulk phase migration kinetics. CSFN0.1 exhibits the lowest LF peak area, indicating that 10 mol% is close to the optimal Cs 1+ Doping content. This content better alleviates the competitive adsorption of CO2 and CO on the active sites of the electrode surface. In addition, we can also conclude that the adsorption and dissociation of CO2 are the rate-controlling steps of the electrode reaction.

[0071] 12. Single electrolytic cell electrolysis performance test

[0072] We conducted CO2 electrolysis activity tests using a single electrolytic cell supported by LSGM electrolyte. Fig.12 The current density at 1.6V, 850, 800, 750, and 700°C is compared in Fig. Fig.12 As shown in b, we can see that CSFN0.1 has the highest current density among all materials. At 1.6 V, 850, 800, 750, and 700 °C, the current densities are 2200, 1330, 818, and 530 mA cm, respectively. -2 ( Fig.12 c). Fig.12 The polarization resistance of each cathode at 1.6 V and 850 ° C is compared. The polarization resistances of SFN, CSFN0.05, CSFN0.1 and CSFN0.15 are 0.35, 0.3, 0.18 and 0.24 Ω cm, respectively. 2 The above results show that Cs 1+ The doping of is beneficial to reduce the impedance of strontium iron-based perovskite oxide as the cathode of SOEC.

[0073] 13. Single electrolytic cell stability test

[0074] We tested the short-term stability of single electrolytic cells with SFN and CSFN0.1 cathodes at 800°C and different current densities. Fig.13 As shown in a, as the applied current density increases from 600 mA cm-2 Increase to 1200mA cm -2 , CSFN0.1 exhibits a more stable operating voltage than SFN cathode. For example, at a current density of 1200 mA cm -2 When the applied voltage on the CSFN0.1 cathode increases from 1.43 V to 1.47 V, while the applied voltage on the SFN cathode increases from 1.65 V to 1.77 V. In addition, at the same current density, the applied voltage on the CSFN0.1 electrolytic cell is lower compared to that on the SFN, indicating that the Cs 1+ The catalytic activity of CO2 electrolysis was improved after doping. We then tested the catalytic activity of CO2 electrolysis at 800 °C, 600, 800, 1000 and 1200 mA cm -2 The CO yield and the corresponding Faraday efficiency were tested at a current density of . Fig.13 As shown in Figure b, the Faraday efficiencies of CSFN0.1 and SFN are both close to 100%, indicating that there are no problems such as carbon deposition and gas leakage during the operation of SOEC. Then we conducted a long-term stability test on the CSFN0.1 electrolytic cell. Fig.13 As shown in c, at 800°C and an applied current density of 600 mA cm -2 The electrolytic cell ran stably for 100 h, which was attributed to the stable catalytic activity and anti-carbon deposition performance of CSFN0.1. After the stable operation, we studied the carbon deposition on the electrode by Raman spectroscopy. Fig.13 As shown in (d), no obvious CC bond structure was observed in the Raman spectrum, which indicates that no carbon deposit was formed on the electrode.

Claims

1. A cesium ion-doped strontium iron-based perovskite solid oxide electrolytic cell cathode material, characterized in that: It has the following chemical formula: Cs x Sr y Fe z Nb m O 3-δ , δ is the oxygen vacancy; 0.05≤x≤0.15, 0.85≤y≤0.95, 0.85≤z≤0.95, 0.05≤m≤0.

15.

2. The cathode material according to claim 1, characterized in that The chemical formula is Cs 0.1 Sr 0.9 Fe 0.9 Nb 0.1 O 3-δ .

3. The method for preparing the cathode material according to claim 1, characterized in that: It is prepared by the sol-gel method.

4. The preparation method according to claim 3, characterized in that: In the sol-gel method, citric acid is first dissolved in deionized water, and then niobium oxalate is added. After the dissolution, strontium nitrate, cesium nitrate, and ferric nitrate are dissolved. Then, a solution of ethylenediaminetetraacetic acid dissolved in ammonia water is added to the above-mentioned metal ion solution. The water is evaporated under heating and stirring conditions to obtain a gel-like substance. The gel-like substance is placed in an oven for drying to obtain a material precursor, and then the precursor is placed in a muffle furnace for calcination to obtain a phased powder.

5. The preparation method according to claim 4, characterized in that: The conditions of the calcination process are: calcination temperature is 950-1050°C, and calcination time is 3-8 hours.

6. The preparation method according to claim 4, characterized in that: The total molar ratio of ethylenediaminetetraacetic acid, citric acid and metal ions is 2:0.8-1.2:0.8-1.

2.

7. The preparation method according to claim 4, characterized in that: The drying temperature of the precursor is 150-200°C and the drying time is 3-8 hours.

8. Use of the solid oxide electrolytic cell cathode material according to claim 1 in the electrolysis of CO2.

9. The use according to claim 9, characterized in that: The electrolyte used is La 0.8 Sr 0.2 Ga 0.8 Mg 0.2 O 3-δ The anode is Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ .

10. A method to improve SrFe 0.9 Nb 0.1 O 3-δ The method of improving the oxygen vacancies on the surface of the material or the adsorption and dissociation properties of CO2 is to dope cesium ions into the oxide.